Anesthetic Management of Mechanical Thrombectomy for Acute Ischemic Stroke with Severe Mitral Stenosis: A Case Report - MD, Burhan; Suarjaya, I Putu Pramana; Ratu, Tiffani; Wiryawan, I Nyoman; MD, Patricia; Tini, Kumara (Jurnal Neuroanestesi Indonesia, 2025)
Acute ischemic stroke from large vessel occlusion requires prompt reperfusion to preserve brain function. Mechanical thrombectomy is the treatment of choice in selected cases, especially cardioembolic strokes. Anesthetic management plays a critical role, particularly in patients with cardiac comorbidities. We report a 62-year-old woman presenting with left-sided weakness and reduced consciousness, six hours prior to admission. She had a history of rheumatic mitral stenosis and atrial fibrillation. CT angiography showed infarction in the right MCA territory with distal ICA occlusion. Intravenous thrombolysis was initiated but failed to show improvement. Mechanical thrombectomy was then performed under general anesthesia. Due to the patient’s decreased consciousness and aspiration risk, general anesthesia was preferred to secure the airway and allow precise hemodynamic control. The anesthetic strategy focused on maintaining systemic vascular resistance while avoiding increased pulmonary vascular resistance to prevent right heart overload in mitral stenosis, also oxygenation and ventilation were carefully managed to avoid hypoxia and hypercapnia. Full vessel recanalization (mTICI 3) was achieved without complication. This case highlights the importance of tailoring anesthesia to individual risk profiles, particularly in stroke patients with valvular heart disease, where general anesthesia may provide optimal safety and procedural success.